A MODIFIED GIEMSA STAINING TECHNIQUE FOR EVALUATION OF ACROSOME INTEGRITY OF FROZEN SEMEN - MANOKARAN, S; PATEL, SH; NIKHATE, R V; CHAUDHARI, N N; SHUKLA, H R (The Indian Journal of Animal Reproduction, 2023)
A simplified technique to evaluate the acrosome integrity using Giemsa stain in frozen semen doses at roomtemperature was discussed.
Keywords: Acro$ome integrity; Giemsa stain; Frozen semen